Effectiveness of sports activities in Reducing Physical Abusive Behavior with 12-Year-Old Pupils in Ezzedine Al-Qassam school, Jableh City (an Experimental Study) (Journal of Hama University, 2022)
SThe current study aims to verify the effectiveness of the programme of sports activities at reducing the physical aggressive behavior of 12-year-old pupils at the Izz al-Din al-Qassam School in Jabalah city of the Directorate of Education in Latakia governorate. The study was Conducted on a group of pupils showing some aggressive behavior, the pilot group included 12 pupils with aggressive behavior. The results showed the effectiveness of the sports-based programme and its positive impact at reducing the physical aggressive behavior of the pupils' target sample.
Keywords: Key words: (Physical Training, abusive behavior, 12-year-old ppupils).